AIICN: a 7G multi-path transmission based on information-centric network - Xing, Ziyang (Frontiers in Computer Science, 2025)
The 7G network refers to the seventh generation of mobile communication standards, which will integrate satellites, airships, and base stations to achieve data transmission with longer coverage. It can also be deeply integrated with artificial intelligence, big data, and other technologies. Multi-path transmission achieves bandwidth aggregation by establishing multiple paths between the sender and the receiver, improving transmission reliability and data accessibility. Therefore, it is of great significance to apply multi-path transmission to 7G networks. However, traditional multi-path transmission technologies (MPTCP/MPQUIC) cannot cope with the new features emerging in 7G networks, such as path selection, low latency, and protocol incompatibility, which require lower complexity. The Information-Centric Network (ICN) offers the advantages of strong mobility and bandwidth efficiency and has been widely adopted in integrated networks. Therefore, this study proposes an artificial intelligence multi-path transmission mechanism based on the ICN and mathematically models the entire transmission process as a mixed-integer linear programming model to solve the problem of multi-path transmission path conflicts in 7G networks (called AIICN). Experiments demonstrate that the proposed AIICN multi-path transmission offers advantages of high throughput, low complexity, and fast algorithm convergence, with a transmission throughput approximately 21% higher than that of traditional multi-path transmission. AIICN can be well applied to 7G networks to achieve efficient multi-path transmission.